POLITIK HUKUM TINDAK PIDANA POLITIK UANG DALAM PEMILIHAN UMUM DI INDONESIA - Satria, Hariman (Komisi Pemberantasan Korupsi, 2019)
Criminal acts of money politics are regulated in Article 523 paragraph (1) to paragraph (3) Law No. 7 of 2017 concerning Elections which is divided into three categories, namely during the campaign, the period of calm and the period of voting. When noted, there are relatively similarities the elements of actus reus in paragraph (1) to paragraph (3) in the article. As for the rea method, it was formulated deliberately. Prevention of criminal acts of money politics can be done through the criminology perspective crime prevention doctrine which focuses on five theories, namely abolitionistic theory, emphasizing the driving factors of crime; a moralistic theory that emphasizes community enlightenment through moral messages; and the theory of primary, secondary and tertiary prevention. Political parties should participate in criminal liability when involved in acts of money politics by referring to the identification theory. Keywords: Legal Politics, Criminal Act, Money Politics, General Election